Influence of University Education on Changes in Students’ Value Orientations - Z. V. Puzanova; Т. I. Larina (Высшее образование в России)
Value orientations of young people are an issue that does not lose relevance in the agenda of  social and humanitarian  sciences and youth policy. Students are the driving  force of youth. Having  activity  and  reactivity,  as well  as  a  certain  intellectual background, namely  students  can stimulate social transformations. The University, as an agent of socialization, carries out not only educational activities, but also pedagogical and socializing work, that is why it is able to influence on the development of values and characteristics of students. The article is an analytical review of the data of a unique monitoring conducted since 2015 at the RUDN University in order to assess the effectiveness of pedagogical work at the University. In 2015 and 2019, 60% of 1st-year and 4th-year (graduate) students were surveyed using online questionnaires, respectively, which represents a quasi-panel. The theoretical framework is determined by the concept of M. Rokich about instrumental and terminal values, as well as Yu.A. Zubok’s and V.I. Chuprov’s concept about meaning-in-life values. The article presents data related to the value orientations of Russian students in the context of their changes in the course of study at the University, namely, issues of patriotism, life values, “idols” as models that students strive for, as well as personal characteristics, which determine the value orientations and other characteristics of an individual (instrumental). The main conclusion: life values and value orientations remain almost unchanged after 4 years of training, while personal characteristics may change throughout the process of training and education. The University can also affect such values as patriotism and the presence of an “idol”. For students of the RUDN University, the questions of patriotism are “difficult”, and idols are most often either family members or no one at all, which is confirmed by data from other surveys. The proposed conceptual model of monitoring may be of interest to employees of other universities and specialists in the field of education, youth work and youth sociology.